Pengelolaan Masjid Berbasis Kampus dalam Meningkatkan Pemberdayaan Masyarakat - Egidiasafitri, Egidiasafitri; Kuswana, Dadang (Tadbir: Jurnal Manajemen Dakwah, 2021)
This research aims to determine the management of campus-based mosques in improving community empowerment, through the planning process, organizing, actuating, and controlling of activities in building cooperation with the community, so that all the empowerment carried out by DKM mosques can run effectively and efficiently. The method used in this research uses descriptive methods with a qualitative approach. The research at the Al-Jabbar Mosque in the ITB Jatinangor Campus can be obtained from the management data of the Al-Jabbar mosque covering several stages in arranging the planned program of activities. There are several steps used in empowering the community through the Al-Jabbar mosque in accordance with the management functions used. First is program planning carried out by the DKM Al-Jabbar mosque in improving community empowerment. Second, organizing is applied to the division of work tasks to DKM administrators. Third, the implementation is implemented through guidance, giving motivation to the board, having a relationship. Then the last is the supervision applied by the Al-Jabbar DKM mosque through direct and indirect supervision.